Optimization and Efficiency Comparison of Dispersive and Cartridge Solid Phase Extraction Cleanup Techniques in the Analysis of Pesticide Residues in Some Vegetables Using Gas Chromatography-Mass Spectrometry - Alnedhary, Anass A.; AL-Hammadi, Mahfoudh M.; Numan, Abdualqawi A.; Murshed, Fatima A. (PSM Biological Research, 2020)
This work was conducted to demonstrate the optimization procedures and results for a sample of preparation method combining Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction with cartridge solid phase extraction (c-SPE) cleanup utilized for the analysis of pesticides residues in some vegetables using gas chromatography-mass spectrometry (GC-MS). The method applied for the analysis of four pesticides of different classes; dimethoate (Organophosphorus), fenvalerate (Pyrethroid), difenoconazole (Triazole) and deltamethrin (Pyrethroid) on four types of vegetables (i.e. tomato, potato, cucumber, and carrot). The procedures simply involve the use of acetonitrile containing 1% acetic acid for the extraction, and for cleanup; a manually prepared solid-phase extraction cartridge containing primary secondary amine (PSA) and normal charcoal were used. The validated GC-MS analysis method for the pesticide residues in the selected vegetables has high linearity with R2 ranged from 0.9965 to 0.9999. The precision of the method estimated as relative standard deviation (%RSD) was ? 9.4% for all target pesticides which were indicative of the high repeatability of the optimized method. The accuracy calculated as average recoveries (%R) was between 80.52% and 99.63%. LODs for target pesticides in spiked cucumber, tomato, carrot, and potato samples ranged between 0.0950 and 0.5590 ng/g. The combined sample preparation method is cost-effective and has shown good simplification, recovery and cleanup capacity and proved to be efficient and suitable for the proposed application.